Perancangan Konverter DC ke DC untuk Menstabilkan Tegangan Keluaran Panel Solar Cell Menggunakan Teknologi Boost Converter - Suwitno, Suwitno; Rahayu, Yusnita; Amri, Rahyul; Hamdani, Eddy (JET (Journal of Electrical Technology), 2017)
Efforts and strategies have been done both by the providers of electrical energy and the government to handle the increase in electricity demand.  However, there has been no satisfactory result. The government has set a major policy on energy management, namely conservation and energy diversification in order to reduce dependence on non-renewable energy sources and utilize renewable energy available in areas where power plants will be built to meet the growing demand for electricity. Riau Province in addition to located in tropical climates and many of its areas are on the coast that its existence is very far for affordable network of PLN electricity, therefore the provision of solar power plant is one appropriate alternative, to meet the needs of electrical energy for the needs of the population. While the output voltage generated by solar cells is not constant, but it depends on the natural conditions that at any time vary the intensity of sunlight, so that the output voltage of the solar cell is also not constant and varies throughout the daytime. In general, commercial equipment has specification limits for ± 10% voltage variation. Disturbances such as voltage varization, if not handled seriously can cause damage to consumer electrical equipment, in addition to the use of electrical energy, in the form of varying output voltage resulting in expensive cost. To overcome the problem of voltage variations produced solar cell can be used prototype dc to dc converter using boost converter technology, which  automatically  adjust  the  output  voltage  according  to  the  desired  voltage.Designing  DC  to  DC Converters To Stabilize Solar Cell Outputs Using Boost Converter Technology has been tested for performance through the output voltage of a 100 WP solar cell panel whose values vary from 13.5 volts to 20.8 volts as a boost converter input and produce a regulated output voltage 24 volt. Based on the results of prototype testi ng dc to dc converter using booast converter technology that has been designed to produce a voltage regulated voltage of 24 volts direct current declared valid. The valid intent here because the output voltage is still dirange 24 volts ± 10%.